A new counterintuitive training for adult amblyopia. Issue 2 (28th December 2018) - Lunghi, Claudia; Sframeli, Angela T.; Lepri, Antonio; Lepri, Martina; Lisi, Domenico; Sale, Alessandro; Morrone, Maria C.
Abstract: Objectives: The aim of this study was to investigate whether short‐term inverse occlusion, combined with moderate physical exercise, could promote the recovery of visual acuity and stereopsis in a group of adult anisometropic amblyopes. Methods: Ten adult anisometropic patients underwent six brief (2 h) training sessions over a period of 4 weeks. Each training session consisted in the occlusion of the amblyopic eye combined with physical exercise (intermittent cycling on a stationary bike). Visual acuity (measured with ETDRS charts), stereoacuity (measured with the TNO test), and sensory eye dominance (measured with binocular rivalry) were tested before and after each training session, as well as in follow‐up visits performed 1 month, 3 months, and 1 year after the end of the training. Results: After six brief (2 h) training sessions, visual acuity improved in all 10 patients (0.15 ± 0.02 LogMar), and six of them also recovered stereopsis. The improvement was preserved for up to 1 year after training. A pilot experiment suggested that physical activity might play an important role for the recovery of visual acuity and stereopsis. Conclusions: Our results suggest a noninvasive training strategy for adult human amblyopia based on an inverse‐occlusion procedure combined with physical exercise.